A pilot study of interprofessional palliative care education of medical students in the UK and USA. Issue 1 (21st June 2017) - Gadoud, Amy; Lu, Wei-Hsin; Strano-Paul, Lisa; Lane, Susan; Boland, Jason W
Abstract : Background: Educating medical students to care for patients at the end-of-life is increasingly recognised as an essential component of training. Traditionally, medical student programmes are run by doctors, but patient care is delivered by an interprofessional team. Our programmes in the UK and USA independently developed a teaching experience led by an interprofessional team of palliative care health professionals. Objectives: This study explores the palliative care health professionals' perceptions, regarding their unique role in medical student palliative care education. Methods: This is the first study to ascertain views of an interprofessional team delivering palliative care education to medical students. Focus groups enable interaction between members of the group as well as the generation of consensus of comments among group members. Results: Two major themes were identified: perceived benefits and value of the experience, and the challenges and lessons learnt from the experiences. Conclusions: Despite different structures and settings, this experiential learning in palliative care provided a rewarding interprofessional experience that has historically been difficult to achieve.